Living With Cognitive Impairment in China: Exploring Dyadic Experiences Through a Person-Centered Care Lens. (March 2021) - Wang, Jing; Corazzini, Kirsten N.; McConnell, Eleanor S.; Ding, Ding; Xu, Hanzhang; Wei, Sijia; Wu, Bei
China has experienced a substantial increase in the number of older adults with dementia and milder forms of cognitive impairment. Being spouses of Persons with cognitive impairment (PWCI) and living with them for several decades does not necessarily mean that it is easier for them to provide person-centered care and maintain a valued and healthy relationship. The current study explored how elements of PCC, as operationalized by the Senses Framework, operate or fail to operate in the dyadic experiences of PWCI and their spousal care partners within the socio-cultural context of China. Our findings suggest that PWCI and their spouses experience the six senses through the person-centeredness in their daily interactions with each other. It also indicated successes and challenges to being person-centered early in the disease and identified their unmet needs as well as barriers and facilitators to improve their well-being.